Mengurai Faktor Terpenting Pada Kualitas Pelayanan Pembiayaan Murabahah Pada Bank Perkreditan Rakyat Syariah - Hafid Aditya Pradesa; Iin Agustina; Pepi Zulvia (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
The quality of service perceived by users has been generally reviewed and researched previously. This study aims to describe the important factors that reflect the quality of service in murabahah financing of a Islamic Rural Bank (BPRS) AM which is operating in Bandung Regency. A total of 140 respondents who are customers of BPRS AM in Bandung Regency are the samples in this study. Two-level confirmatory factor analysis (second order factor analysis) is used to answer the research question posed in this study, namely what are the most important aspects that can be reflected in murabahah services for customers. Factor analysis is used to test the factor weight values of each indicator of the variables observed in the study. The results of data analysis reveal that the quality of murabahah financing services can be well reflected in the aspects of guarantees of trust, responsiveness, price, physical evidence, and reliability provided to murabahah financing customers. In addition, the murabahah service model has a level of validity that can be well confirmed. Findings also reveals that respondents perceive the quality of murabahah services as being in the moderate category. Among five dimensions of murabahah service quality, the aspect of physical evidence was found to be the most important factor in reflecting the quality of murabahah services of BPRS AM operating in Bandung Regency. On the other hand, the respondent's assessment also shows that the aspect of guarantee or trust is the aspect that is rated the highest in murabahah services. In addition to the generally well-confirmed model, the findings of this study are useful as a basis for further exploration of the concept of service quality in Islamic Rural banks.